Lingüística del dolor - Bah, Eлeна (Eslavística Complutense, 2004)
This paper examines verbal expressions of pain in Russian and establishes a comparison with the similar expressions in Spanish. "Pain" has been defined as a psychophysiological phenomenon.. The forms of verbal expression of this feeling/emotion including silence, interjections, significant words, word combinations, expressions, set phrases and metaphors are studied here, highlightening a similarity between the mechanisms of verbal expression of fear and pain. The final analysis of the Spanish word angustia (anguish) includes a search for its equivalents in the Russian language.
Keywords: Pain; Suffenng; Dual nature of words; Verbal extemalization; Anguish